Acceptance of Influenza Vaccination among Pregnant Women during COVID-19 Pandemic in Nonthaburi Province - นับถือดี, กษมา; สัตยสมบูรณ์, ยุวนุช; คงศีล, สุคนธา; ศีลบุตร, จุฑาธิป (Journal of Health Science of Thailand, 2023)
This cross-sectional study aimed to investigate the rate of acceptance for seasonal influenza vaccination (flu vaccine) and to examine factors associated with accepting to get flu vaccine among pregnant women in Nonthaburi Province, during Covid-19 pandemic. The samples were pregnant Thai women eighteen years old or older, and had pregnancy health check up at hospitals. The total of three hundred ninety-six pregnant women from 3 hospitals; one regional hospital and two community hospitals during 2020, June to August were selected by stratified random sampling. Data were collected by using a self-administered questionnaire; and were analyzed by using descriptive statistics, Chi-square test and multiple logistic regression at 0.05 level of significance. The results showed that the average age of the sample was 26.6±6.6 years, gestational age 28-42 weeks was at 56.1 percent, the acceptance rate to get flu vaccine was 61.4 percent, the factors associated with acceptance to get flu vaccine were had flu shot before pregnancy with adjusted Odd Ratio (AOR) = 2.75, 95%CI=1.71-4.42, perceived benefits (AOR=1.84, 95%CI=1.06-3.22), perceived barriers (AOR=2.49, 95%CI=1.52-4.06), family advice (AOR=1.78, 95%CI=1.01-3.14), and perceived policy (AOR=1.79, 95%CI=1.10-2.90). Based on the results, we recommend that policy makers and hospital administrators should design interventions to increase acceptance of the influenza vaccine among pregnant women focusing on the communication of the policy and benefits of influenza vaccination to women and the families.